Beyond the politics of theological despair - Robbins, Jeffrey W. (The journal of religion & society, 2006)
This paper critically explores the political theology of Carl Schmitt. It argues that Schmitt’s analysis, which links the transcendence of God with the political concept of sovereignty, is both too nostalgic and too severe. In the place of Schmitt’s political theology that disdains democracy for the failures of modern liberalism, this paper instead draws on the recent collaborative works of Michael Hardt and Antonio Negri to make the case for a more thoroughgoing commitment to democracy, a commitment that goes beyond the modern liberal concept of popular sovereignty by appealing to the disparate and sometimes unruly voices of the multitude.